ANALISIS FAKTOR YANG BERPENGARUH TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2009-2012 - Chita Kartika Santoso, 10.05.52.0044; Suwarti, Titiek (Students Journal of Accounting and Banking, 2015)
This study aims to transform and the analyze the efect of theÂ Loan to Deposit Ratio (LDR), Net Profit Margin (NPM), Earning Per Share (EPS), and operating Expenses Operating Income (BOPO) to the stock price on the banking companies listed in Indonesia Stock Exchage period 2009-2012. In this study, researchers used data population banking financial companies listed on the Stock Exchange during 2009-2012. The method used is purposive sampling method. Test equipment in this study using multiple linear regression, partial test (t test) and a simultaneous test of f (fÂ test). The result of this study is the Loan to Deposit Ratio,Â Net Profit Margin and operating Expanses Operating Income does not effect the stock price, while earning per share positive effect on stock prices.Keywords: Loan to Deposit Ratio (LDR), Net Profit Margin (NPM), Earning Per Share (EPS), dan Biaya Operasional Pendapatan Operasional (BOPO)